“I never made it to the pros…” Return to sport and becoming an elite athlete after pediatric and adolescent anterior cruciate ligament injury: current evidence and future directions - Hamrin Senorski, Eric; Seil, Romain; Svantesson, Eleonor; Feller, Julian A.; Webster, Kate E.; Engebretsen, Lars; Spindler, Kurt; Siebold, Rainer; Karlsson, Jón; Samuelsson, Kristian (Knee surgery, sports traumatology, arthroscopy, 2018)
The management of anterior cruciate ligament (ACL) injuries in the skeletally immature and adolescent patient remains an area of controversy in sports medicine. This study, therefore, summarizes and discusses the current evidence related to treating pediatric and adolescent patients who sustain an ACL injury. The current literature identifies a trend towards ACL reconstruction as the preferred treatment option for ACL injuries in the young, largely justified by the risk of further structural damage to the knee joint. Worryingly, a second ACL injury is all too common in the younger population, where almost one in every three to four young patients who sustain an ACL injury and return to high-risk pivoting sport will go on to sustain another ACL injury. The clinical experience of these patients emphasizes the rarity of an athlete who makes it to elite level after a pediatric or adolescent ACL injury, with or without reconstruction. If these patients are unable to make it to an elite level of sport, treatment should possibly be modified to take account of the risks associated with returning to pivoting and strenuous sport. The surveillance of young athletes may be beneficial when it comes to reducing injuries. Further research is crucial to better understand specific risk factors in the young and to establish independent structures to allow for unbiased decision-making for a safe return to sport after ACL injury. Level of evidence V.
Published online: 29 November 2017
Gesehen am 25.09.2019